Experiental Learning: Telaah tentang Pola Pendekatan Pembelajaran Kontemporer - M. E. Hidayatullah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Traditional teaching approach is teacher (teacher directive), while the contemporary approach is focused on the role of the learners (experience-based instruction) in achieving the goals of behavior, which is known through direct experience with the approach of experiential learning. Contemporary approach is expected to increase the understanding and the quality of the lesson learned. This paper will review the approach to experiential learning, and several methods of teaching. Keywords: Contemporary Learning, Experiential, Studying Process, Teaching Process.